STUDY OF ADDED VALUE IN TOFU FLOUR PROCESSED PRODUCTS FROM DIFFERENT SOYBEAN VARIETIES FOR FAMILY FOOD SECURITY - Nurwantara, Ma'ruf Pambudi; Wardani, Ratna Mustika; Wuryantoro, Wuryantoro; Puspitawati, Indah Rekyani (Program Studi Agribisnis bekerja sama dengan PERHEPI, 2023)
This research aims to determine the income from processing tofu into tofu flour originating from soybeans of the Wilis variety, Baluran variety, and imported varieties in the research area and to analyze the added value obtained from processing tofu into tofu flour for various soybean varieties (local and imported). Data collection was carried out using the Purposive Sampling Method (Deliberately). The research results show that the income obtained from processing tofu into tofu flour from tofu originating from the Wilis variety is IDR. 995,000,-, then tofu from the Baluran variety of soybeans is IDR. 890,000,-, while tofu originating from imported variety soybeans is IDR 1,040,000,-. The added value obtained from processed tofu flour from Wilis variety soybeans is IDR. 54,250-/kg, followed by tofu flour from the Baluran variety amounting to Rp. 51,250,-/kg originating from the imported variety amounting to Rp. 39,900/kg. Because the output and raw material prices determine the added value ratio, the value-added ratio obtained for tofu flour from the Wilis variety is 81.27%, the Baluran variety is 80.39%, and the imported variety is 79.16%..